The Effect of IFRS 13 Implementation on Corporate Sustainability and the Quality of Accounting Information: Evidence from Emerging Economies - Dawood, Mohammed Salman; Kazem, Sumaya Ali; Ali, Zahraa Abdul- Hamza; Wahhab, Asaad (Technium Social Sciences Journal, 2025)
Applying international financial reporting standards guarantees that companies achieve efficiency and transparency for all public companies in all parts of the advanced world. Some countries with emerging markets have recently moved to apply it, including the Republic of Iraq, which was approved in 2016 and will be effective on the final accounts for the year ending 12/31/2021. Despite the difficulties some companies face in the application, it has become more flexible. The fair value standard IFRS 13 is one of the most important standards that faced challenges in its application due to the difficulty of determining fair value in the Iraqi market due to economic fluctuations and instability of financial markets. Accordingly, the current study aims to know the impact of applying the fair value standard in Iraqi companies on the sustainability of companies and the quality of accounting information. A questionnaire consisting of three axes was developed to achieve the study’s objectives. The first axis was allocated to the independent variable, the application of IFRS 13 in Iraqi companies. In contrast, the second axis was allocated to measuring sustainability, and the third axis was allocated to measuring the quality of accounting information. The questionnaire was distributed randomly to 131 accountants and auditors, including companies included in the application of international financial reporting standards and listed on the Iraq Stock Exchange. The SPSS program version 26 was used to analyse the data and test the hypotheses, and simple and multiple regression were used. The research concluded that companies’ commitment to the IFARS 13 standard would achieve sustainability due to a strong correlation between them, according to the Pearson Correlation, of 0.85. At the same time, there was an average relationship of 0.523 between the IFRS 13 standard and the quality of accounting information, but it achieved a significant significance of 0.00.